Temporal Expectation Enhances Contrast Sensitivity by Phase Entrainment of Low-Frequency Oscillations in Visual Cortex - Cravo, André M. (Society for Neuroscience, 2013)
Although it is increasingly accepted that temporal expectation can modulate early perceptual processing, the underlying neural computations remain unknown. In the present study, we combined a psychophysical paradigm with electrophysiological recordings to investigate the putative contribution of low-frequency oscillatory activity in mediating the modulation of visual perception by temporal expectation. Human participants judged the orientation of brief targets (visual Gabor patterns tilted clockwise or counterclockwise) embedded within temporally regular or irregular streams of noise-patches used as temporal cues. Psychophysical results indicated that temporal expectation enhanced the contrast sensitivity of visual targets. A diffusion model indicated that rhythmic temporal expectation modulated the signal-to-noise gain of visual processing. The concurrent electrophysiological data revealed that the phase of delta oscillations overlying human visual cortex (1–4 Hz) was predictive of the quality of target processing only in regular streams of events. Moreover, in the regular condition, the optimum phase of these perception-predictive oscillations occurred in anticipation of the expected events. Together, these results show a strong correspondence between psychophysical and neurophysiological data, suggesting that the phase entrainment of low-frequency oscillations to external sensory cues can serve as an important and flexible mechanism for enhancing sensory processing.